The effect of G418 and PTC124 as suppression therapy for Beta Thalassemia - Estima, Cláudia Filipa de Noronha (2016)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2016